Seismic input optimisation for Joint Migration Inversion on complex structures, Malay Basin - Hairi, H.H. (Institute of Physics Publishing, 2017)
The field of seismic imaging has made a recent breakthrough in migration technique with the introduction of Joint Migration Inversion to aid the imaging process by incorporating multiple scattering into the algorithm. Initially, seismic multiples have been regarded as noise and should be removed prior to migration, but today these multiples could be used to enhance the final seismic images since they carry a vast percentage of energy that was generated from the source during acquisition phase. This new technique could be used to improve the final image of complex structures such as the steeply fractured basement reservoir in Anding Utara Field in Malay Basin. As of now, the efforts of improving the steeply-fractured basement image have been done without the incorporation of multiple scattering. Thus, the application of JMI might shed some light on the potential of this technique. Joint Migration Inversion make use of a Closed-Loop imaging process which means that less wave energy is wasted during processing making the final image more consistent with the input data. In conventional migration process, multiple scattering is removed thus vast amount of energy is wasted that leads to a poor final subsurface image. The two main elements in Joint Migration Inversion are Full-Wavefield Migration and Full-Wavefield Inversion. Apart from including seismic multiples in the imaging process, Joint Migration Inversion also allows the user to automatically update the velocity model of the area under investigation while maintaining very little user intervention. © Published under licence by IOP Publishing Ltd.